A STUDY ON PEOPLE’S FAITH ON RELIGIOUS RITUALS AND CEREMONIES - R.KESAVAPRIYA, Dr.S.Selvaraju (International Journal of Advanced Science and Technology, 2020)
Religious belief is an important factor and a parameter to set human being’s life in an ethical way which is not in the case of life of other animals. Religious belief has been a stable and wide reaching force in human culture. The main objectives of the paper are to find the faith on the religious rituals and ceremonies and also to measure the level of participation of people in religious rituals and ceremonies.The researcher has followed the empirical research and conducted survey among 550 people in Chennai by convenient sampling method. The collected data were analysed by using SPSS software. Mainly compound and multi bar charts were used to analysis the responses of the respondents. From the analysis that can be observed that male respondents have more religious faith than female. Further it can be observed that as the learned people have religious faith than others. The conclusion of the research is that religious belief as a progressive impact in impairing the conduct of the society.